Pre-lithiation binder as well as preparation method and application thereof

The prelithiated binder formed by crosslinking natural polysaccharides, epoxychloride and lithium salts solves the problem of low initial Coulomb efficiency of silicon-based negative electrodes, and achieves high energy density and structural integrity of lithium-ion batteries, and has a green process. Environmental friendly.

CN119220202APending Publication Date: 2024-12-31CHINA ENFI ENG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374727.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The initial Coulombic efficiency of the silicon-based negative electrode material is low, which limits its high energy density performance in lithium-ion batteries. The existing binder has poor bonding effect on the silicon-based negative electrode, and the first-circle Coulombic efficiency is still low.

Method used

Prelithiated binder formed by cross-linking natural polysaccharides, epoxychlorohydrin and lithium salts is used to form a three-dimensional network polymer through cross-linking reaction, which improves the bonding performance of silicon-based negative electrode and initial Coulomb efficiency, and reduces the loss of lithium ion of positive electrodes .

Benefits of technology

It significantly improves the first-circle Coulomb efficiency of the silicon-based negative electrode and the energy density of the lithium-ion battery, improves the integrity of the negative electrode structure, and has a green and environmentally friendly process, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068396140000081
    Figure BDA0005068396140000081
  • Figure BDA0005068396140000091
    Figure BDA0005068396140000091
Patent Text Reader

Abstract

The invention provides a pre-lithiation binder as well as a preparation method and application thereof. The pre-lithiation binder comprises the following raw materials: natural polysaccharide, epichlorohydrin and lithium salt. The silicon-based negative electrode binder for the lithium ion battery is a three-dimensional network polymer formed by crosslinking natural polysaccharide, epichlorohydrin and lithium salt, the binder has good binding performance due to the complex network structure, and the integrity of a negative electrode structure can be kept; meanwhile, by introducing the lithium salt, the initial coulombic efficiency of the silicon-based negative electrode can be effectively improved, the lithium ion loss of the positive electrode can be reduced, and the high energy density of the silicon-based material can be developed, so that the energy density of the lithium ion battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a pre-lithiation binder and a preparation method and application thereof. Background Art

[0002] With the development of electric vehicles, the demand for lithium-ion batteries is increasing. The negative electrode materials of lithium-ion batteries include silicon, tin, copper, aluminum, nickel, titanium, etc. Among them, silicon-based negative electrode materials have the advantages of high capacity, low cost, and environmental friendliness, and are one of the most studied negative electrode materials. The theoretical specific capacity of silicon-based negative electrode materials is 4200mAh / g, which is nearly 10 times higher than the theoretical specific capacity of single silicon. However, the initial coulomb efficiency (also known as the first coulomb efficiency, the first cycle coulomb efficiency) of silicon-based negative electrode materials is low, and the cycle performance is poor, which limits the application of silicon-based negative electrode materials. Currently, commercially available binders such as sodium hydroxymethyl cellulose and styrene-butadiene rubber, polyacrylic acid, and sodium alginate, although they work well for graphite negative electrodes, have low initial coulomb efficiency for silicon-based negative electrodes. The initial coulomb efficiency value of silicon-based negative electrodes is generally around 80%, which is lower than that of commercial graphite negative electrodes (90-94%). Such a low initial coulomb efficiency is not conducive to the high energy density of silicon-based electrodes in lithium-ion batteries.

[0003] Patent CN 110085867 A discloses a binder for lithium-ion battery silicon-carbon negative electrode, including a polyacrylic acid (PAA) main binder with a molecular weight of 10w to 300w and metal oxides and lithium hydroxide additives. Patent CN110071289A discloses a lithium-ion battery silicon-based negative electrode composite binder and its preparation method and application, the composite binder includes modified polyacrylic acid PAAH 1-x -Li x and polyionic liquid PIL / TFSI, the polyionic liquid contains bis(trifluoromethylsulfonyl)imide anion.

[0004] However, the above-mentioned binders have poor bonding effect on silicon-based negative electrodes, and the first-cycle coulombic efficiency of silicon-based negative electrodes is still low. Summary of the invention

[0005] The main purpose of the present invention is to provide a pre-lithiation binder and a preparation method and application thereof, so as to solve the problem of low first-cycle coulombic efficiency of silicon-based negative electrodes in the prior art.

[0006] In order to achieve the above object, according to one aspect of the present invention, a pre-lithiation binder is provided, and the raw materials of the pre-lithiation binder include natural polysaccharide, epichlorohydrin and lithium salt.

[0007] Furthermore, the mass ratio of natural polysaccharide to epichlorohydrin is 1:(2-100); and / or the mass ratio of natural polysaccharide to lithium salt is 1:(0.4-20).

[0008] Furthermore, the natural polysaccharide includes one or more of sodium alginate, konjac glucomannan, starch, sodium hyaluronate, xanthan gum, peach gum and gum arabic; preferably, the weight average molecular weight of the natural polysaccharide is 100,000 to 2 million; and / or the lithium salt includes one or more of lithium metaborate, lithium tetraborate and lithium sulfate.

[0009] According to another aspect of the present invention, a method for preparing the above-mentioned pre-lithiation binder of the present invention is provided, comprising the following steps: step S1, mixing natural polysaccharides with water to obtain a first raw material solution, and adjusting the pH of the first raw material solution to 8-10; step S2, mixing lithium salt with water to obtain a second raw material solution; step S3, adding the second raw material solution dropwise to the first raw material solution to obtain a mixed solution; step S4, adding epichlorohydrin to the mixed solution to carry out a cross-linking reaction to obtain a pre-lithiation binder.

[0010] Furthermore, in step S1, the mass fraction of the first raw material solution is 0.1-5%; and / or the natural polysaccharide is mixed with water and then heated in a water bath, and the water bath temperature is 60-90°C; preferably, an alkaline aqueous solution is used to adjust the pH of the first raw material solution, and the alkaline aqueous solution includes a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution; more preferably, the molar concentration of the alkaline aqueous solution is 0.08-0.12 mol / L.

[0011] Furthermore, in step S2, the mass fraction of the second raw material solution is 1-10%; and / or in step S3, the mass ratio of the natural polysaccharide in the first raw material solution to the lithium salt in the second raw material solution is 1:(0.4-20).

[0012] Furthermore, in step S4, the mass ratio of the natural polysaccharide in the first raw material solution to epichlorohydrin is 1:(2-100); and / or the temperature of the cross-linking reaction is 60-90° C., and the time is 4-10 hours.

[0013] According to another aspect of the present invention, there is provided a silicon-based negative electrode plate, comprising the above-mentioned pre-lithiation binder of the present invention.

[0014] Furthermore, the weight percentage of the pre-lithiation binder in the silicon-based negative electrode plate is 5-15%.

[0015] According to another aspect of the present invention, there is provided a lithium-ion battery comprising the above-mentioned silicon-based negative electrode plate of the present invention.

[0016] The silicon-based negative electrode binder for lithium-ion batteries of the present invention is a three-dimensional network polymer formed by cross-linking natural polysaccharides, epichlorohydrin and lithium salts. The complex network structure can make the binder have good bonding properties, which is conducive to maintaining the integrity of the negative electrode structure. At the same time, by introducing lithium salts, the initial coulomb efficiency of the silicon-based negative electrode can be effectively improved, the loss of positive electrode lithium ions can be reduced, and the high energy density of silicon-based materials can be exerted, thereby further improving the energy density of lithium-ion batteries. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0018] As described in the background of the present invention, the prior art has the problem of low first-cycle coulombic efficiency of silicon-based negative electrodes. In order to solve the above problem, in a typical embodiment of the present invention, a pre-lithiation binder is provided, and the raw materials of the pre-lithiation binder include natural polysaccharides, epichlorohydrin and lithium salts.

[0019] The pre-lithiation silicon-based negative electrode binder of the present invention uses natural polysaccharides as raw materials, lithium salts as additives, and epichlorohydrin as a cross-linking agent to form a three-dimensional network polymer through cross-linking. The characteristics of natural polysaccharides being rich in hydroxyl groups are utilized to realize hydrogen bond interactions between polymer molecules. Epichlorohydrin can further open the ring to cross-link the lithium salts and the hydroxyl groups on the natural polysaccharides, so that the binder has good bonding properties. By adding lithium salts to the binder, lithium is compounded in the three-dimensional network formed by cross-linking polysaccharides in the form of ions, thereby improving the first-cycle coulomb efficiency of the silicon-based negative electrode, reducing the loss of positive lithium ions, and being conducive to the high energy density of silicon-based materials, and further improving the energy density of lithium-ion batteries.

[0020] In order to further improve the cross-linking effect of natural polysaccharides and improve the cross-linked network structure to form a binder with better bonding performance, in a preferred embodiment, the mass ratio of natural polysaccharides to epichlorohydrin is 1:(2~100); and / or the mass ratio of natural polysaccharides to lithium salt is 1:(0.4~20), which can provide a more appropriate amount of lithium salt for pre-lithiation, thereby further improving the first-cycle coulombic efficiency of the silicon-based negative electrode.

[0021] In a preferred embodiment, the natural polysaccharide includes one or more of sodium alginate, konjac glucomannan, starch, sodium hyaluronate, xanthan gum, peach gum and gum arabic; preferably, the weight average molecular weight of the natural polysaccharide is 100,000 to 2 million; and / or the lithium salt includes one or more of lithium metaborate, lithium tetraborate and lithium sulfate. The above-mentioned types of natural polysaccharides and lithium salts are more compatible, can form a three-dimensional network polymer with better adhesion, and further reduce the loss of positive electrode lithium ions, and improve the first effect of silicon-based negative electrodes.

[0022] In another typical embodiment of the present invention, a method for preparing the above-mentioned pre-lithiation binder of the present invention is also provided, comprising the following steps: step S1, mixing natural polysaccharides with water to obtain a first raw material solution, and adjusting the pH of the first raw material solution to 8-10; step S2, mixing lithium salt with water to obtain a second raw material solution; step S3, adding the second raw material solution dropwise to the first raw material solution to obtain a mixed solution; step S4, adding epichlorohydrin to the mixed solution to carry out a cross-linking reaction to obtain a pre-lithiation binder.

[0023] The present invention first mixes natural polysaccharides with water, and adjusts the pH of the solution to 8-10 to keep the solution weakly alkaline; then mixes lithium salt with water, drops it into the first raw material solution, and then adds epichlorohydrin to carry out a cross-linking reaction. At this time, epichlorohydrin opens the ring under a weakly alkaline environment, cross-links the hydroxyl groups on the lithium salt and the polysaccharide, and obtains a pre-lithiation binder. The above preparation method is simple and easy to operate. The prepared pre-lithiation binder can further improve the first-cycle coulomb efficiency of the silicon-based negative electrode while having good bonding properties. In addition, traditional polyvinylidene fluoride binders generally use toxic N-methylpyrrolidone as a solvent, which will pollute the environment and cause harm to the human body. The natural polysaccharide raw materials selected by the present invention are widely available in nature, and water is used as a solvent, which is green and environmentally friendly, and the synthesis process is simple, and it is easy to realize industrial production.

[0024] In a preferred embodiment, in step S1, the mass fraction of the first raw material solution is 0.1-5%; and / or the natural polysaccharide is mixed with water and then heated in a water bath, and the water bath temperature is 60-90°C; preferably, an alkaline aqueous solution is used to adjust the pH of the first raw material solution, and the alkaline aqueous solution includes an aqueous sodium hydroxide solution and / or an aqueous potassium hydroxide solution; more preferably, the molar concentration of the alkaline aqueous solution is 0.08-0.12 mol / L. This ensures that epichlorohydrin is fully ring-opened under alkaline conditions, and the lithium salt and the hydroxyl groups on the polysaccharide are more fully cross-linked, thereby obtaining a binder that is more conducive to improving the first-cycle coulomb efficiency of the silicon-based negative electrode.

[0025] Based on similar reasons, in a preferred embodiment, in step S2, the mass fraction of the second raw material solution is 1-10%; and / or in step S3, the mass ratio of the natural polysaccharide in the first raw material solution to the lithium salt in the second raw material solution is 1:(0.4-20). This ensures that the polymer is reacted at an appropriate concentration, making the reaction more complete.

[0026] In order to further increase the reaction rate of the cross-linking reaction and further improve the three-dimensional network of the cross-linked product, in a preferred embodiment, in step S4, the mass ratio of the natural polysaccharide in the first raw material solution to epichlorohydrin is 1:(2-100); and / or the temperature of the cross-linking reaction is 60-90°C and the time is 4-10h.

[0027] In another typical embodiment of the present invention, a silicon-based negative electrode plate is provided, comprising the above-mentioned pre-lithiation binder of the present invention, which has significantly improved plate integrity and significantly improved first-cycle coulombic efficiency.

[0028] Too low a binder content will cause the active material to fall off, and too high a binder content will cause the electrode to curl. In a preferred embodiment, the weight percentage of the pre-lithiation binder in the silicon-based negative electrode electrode is 5-15%, thereby ensuring that the silicon-based negative electrode (such as a silicon-carbon negative electrode) can be stably cycled on the basis of significantly improved first-cycle coulombic efficiency.

[0029] In another typical embodiment of the present invention, a lithium-ion battery is provided, comprising the silicon-based negative electrode plate of the present invention, which has significantly improved first-cycle coulombic efficiency and significantly increased energy density.

[0030] Typically but not limiting, the mass ratio of natural polysaccharide to epichlorohydrin is 1:2, 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100 or a range consisting of any two of them.

[0031] Typically but not limiting, the mass ratio of natural polysaccharide to lithium salt is 1:0.4, 1:1, 1:2, 1:5, 1:10, 1:15, 1:20 or a range consisting of any two of them.

[0032] Typically but not limiting, in step S4, the temperature of the cross-linking reaction is 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, and the time is 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range consisting of any two of them.

[0033] Typically but not limiting, the weight percentage of the pre-lithiation binder in the silicon-based negative electrode plate is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two of them.

[0034] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0035] Example 1

[0036] Step S1, weighing 0.25g of sodium alginate (weight average molecular weight of about 1 million), and dissolving it in deionized water to prepare 50mL of 5% sodium alginate solution, and transferring it to a 100mL four-necked round-bottom flask; placing the flask in a 70°C constant temperature water bath and stirring; then preparing a 0.1mol / L sodium hydroxide solution, slowly adding it dropwise to the round-bottom flask, and adjusting the pH of the solution to about 10;

[0037] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0038] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0039] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0040] Example 2

[0041] Step S1, weigh 0.005g of sodium alginate (weight average molecular weight of about 1 million), and dissolve it in deionized water to prepare 50mL of 0.1% sodium alginate solution, and transfer it to a 100mL four-necked round-bottom flask; place the flask in a 70°C constant temperature water bath and stir; then prepare 0.1mol / L sodium hydroxide solution, slowly add it dropwise to the round-bottom flask, and adjust the pH of the solution to about 10;

[0042] Step S2, weighing 0.1 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0043] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0044] Step S4, add 0.5g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0045] Example 3

[0046] Step S1, weighing 0.25g of sodium alginate (weight average molecular weight of about 1 million), and dissolving it in deionized water to prepare 50mL of 5% sodium alginate solution, and transferring it to a 100mL four-necked round-bottom flask; placing the flask in a 70°C constant temperature water bath and stirring; then preparing a 0.1mol / L sodium hydroxide solution, slowly adding it dropwise to the round-bottom flask, and adjusting the pH of the solution to about 10;

[0047] Step S2, weighing 0.1 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 1%;

[0048] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0049] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0050] Example 4

[0051] Step S1, weighing 0.25g of sodium alginate (weight average molecular weight of about 1 million), and dissolving it in deionized water to prepare 50mL of 5% sodium alginate solution, and transferring it to a 100mL four-necked round-bottom flask; placing the flask in a 70°C constant temperature water bath and stirring; then preparing a 0.1mol / L sodium hydroxide solution, slowly adding it dropwise to the round-bottom flask, and adjusting the pH of the solution to about 10;

[0052] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0053] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0054] Step S4, add 0.5g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0055] Example 5

[0056] Step S1, weighing 0.05g of sodium alginate (weight average molecular weight of about 1 million), and dissolving it in deionized water to prepare 50mL of 1% sodium alginate solution, and transferring it to a 100mL four-necked round-bottom flask; placing the flask in a 70°C constant temperature water bath and stirring; then preparing a 0.1mol / L sodium hydroxide solution, slowly adding it dropwise to the round-bottom flask, and adjusting the pH of the solution to about 10;

[0057] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0058] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0059] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0060] Example 6

[0061] Step S1, weigh 0.25g of sodium alginate (weight average molecular weight of about 1 million), and dissolve it in deionized water to prepare 50mL of 5% sodium alginate solution, and transfer it to a 100mL four-necked round-bottom flask; place the flask in a 90°C constant temperature water bath and stir; then prepare 0.1mol / L sodium hydroxide solution, slowly add it dropwise to the round-bottom flask, and adjust the pH of the solution to about 10;

[0062] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0063] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0064] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0065] Example 7

[0066] Step S1, weigh 0.25g konjac glucomannan (weight average molecular weight is about 1,000,000), and dissolve it in deionized water to prepare 50mL mass concentration of 5% konjac glucomannan solution, which is moved into a 100mL four-necked round-bottomed flask; the flask is placed in a 70°C thermostatic water bath and stirred; subsequently, a 0.1mol / L sodium hydroxide solution is prepared, which is slowly added dropwise to the round-bottomed flask until the pH value of the solution is about 10;

[0067] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 5%;

[0068] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0069] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 70°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0070] Example 8

[0071] Step S1, weigh 0.25g of sodium hyaluronate (weight average molecular weight of about 100,000), dissolve it in deionized water to prepare 50mL of 5% sodium alginate solution, and transfer it to a 100mL four-necked round-bottom flask; place the flask in a 60°C constant temperature water bath and stir; then prepare 0.08mol / L sodium hydroxide solution, slowly add it dropwise to the round-bottom flask, and adjust the pH of the solution to about 8;

[0072] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form a lithium metaborate solution with a mass concentration of 1%;

[0073] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0074] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 60°C for 10h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0075] Example 9

[0076] Step S1, weigh 0.25g xanthan gum (weight average molecular weight of about 2 million), and dissolve it in deionized water to prepare 50mL of 5% sodium alginate solution, and transfer it to a 100mL four-necked round-bottom flask; place the flask in a 90°C constant temperature water bath and stir; then prepare 0.12mol / L sodium hydroxide solution, slowly add it dropwise to the round-bottom flask, and adjust the pH of the solution to about 10;

[0077] Step S2, weighing 0.5 g of lithium sulfate powder and dissolving it in deionized water to form a lithium sulfate solution with a mass concentration of 10%;

[0078] Step S3, slowly adding the lithium sulfate solution into the sodium alginate solution to obtain a mixed solution;

[0079] Step S4, add 1.0g of epichlorohydrin to the mixed solution, continue to stir in a water bath at 90°C for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0080] Comparative Example 1

[0081] Step S1, weighing 0.25g of sodium alginate (weight average molecular weight of about 1 million), and dissolving it in deionized water to prepare 50mL of 5% sodium alginate solution, and transferring it to a 100mL four-necked round-bottom flask; placing the flask in a 70°C constant temperature water bath and stirring; then preparing a 0.1mol / L sodium hydroxide solution, slowly adding it dropwise to the round-bottom flask, and adjusting the pH of the solution to about 10;

[0082] Step S2, weighing 0.5 g of lithium metaborate powder and dissolving it in deionized water to form 10 mL of a lithium metaborate solution with a mass concentration of 5%;

[0083] Step S3, slowly adding the lithium metaborate solution into the sodium alginate solution to obtain a mixed solution;

[0084] Step S4, the mixed solution is stirred in a water bath at 70°C for 4 hours, and then the heating is stopped and the mixture is cooled to room temperature, and then the obtained binder is freeze-dried and ground into powder to obtain a pre-lithiation binder.

[0085] Comparative Example 2

[0086] Prepare 50mL of 5% sodium alginate solution, transfer it to a 100mL four-necked round-bottom flask; place the flask in a 70℃ constant temperature water bath and stir; then prepare 0.1mol / L sodium hydroxide solution, slowly drop it into the round-bottom flask, and adjust the solution pH to about 10; add 1.0g of epichlorohydrin to the above solution, continue stirring in a 70℃ water bath for 4h, then stop heating, cool to room temperature, then freeze-dry the obtained binder, grind it into powder, and obtain a pre-lithiation binder. Prepare freshly before use.

[0087] Comparative Example 3

[0088] Prepare 50mL of 5% sodium alginate solution and transfer it to a 100mL four-necked round-bottom flask; place the flask in a 70℃ constant temperature water bath and stir; then prepare 0.1mol / L sodium hydroxide solution and slowly drop it into the round-bottom flask to adjust the solution pH to about 10; continue stirring in a 70℃ water bath for 4h, then stop heating, cool to room temperature, and then freeze-dry the obtained binder and grind it into powder to obtain a pre-lithiation binder. Prepare freshly before use.

[0089] The binders obtained in the above embodiments and comparative examples are used to prepare silicon-based negative electrode plates and assembled into button-type half-cells. The specific operation is as follows: the mass ratio of silicon-carbon powder (theoretical specific capacity is about 600mAh / g), Super P and binder is 80:10:10 for slurrying, and then the slurry is evenly coated on the copper foil, and the coated electrode is transferred to a 50°C blast drying oven and dried for 2 hours; then the slices are weighed and dried at 100°C under vacuum conditions for 12 hours; the dried electrode is transferred to a glove box, and a lithium sheet is used as a counter electrode to assemble a CR2032 button cell. The assembled battery is left to stand for 12 hours, and then a constant current electrochemical performance test is performed. Among them, the charge and discharge current density is 0.1C, and the voltage range is 0.005~2.0V. The first cycle coulomb efficiency, the first cycle charge specific capacity and the 50-cycle cycle performance are tested respectively, and the electrochemical test results are shown in Table 1. The bonding performance of the binder is tested by performing a 180° peeling test on the electrode and recording the average peeling force of the electrode.

[0090] Table 1

[0091]

[0092]

[0093] It can be seen from Table 1 that the pre-lithiation binder obtained in each embodiment of the present invention can significantly improve the first-cycle coulomb efficiency of a lithium-ion battery using a silicon-based negative electrode, especially in Example 1, the first-cycle coulomb efficiency of the electrode can reach 92%, and the first-cycle coulomb efficiency of Examples 2 to 4 is slightly lower than that of Example 1. This is because Examples 2 to 4 reduce the mass of lithium metaborate, epichlorohydrin and sodium alginate, respectively, so the pre-lithiation degree and viscosity of the binder decrease, resulting in a decrease in the first-cycle coulomb efficiency and a deterioration in the cycle stability, but the above-mentioned decrease is still acceptable in practical applications and is obviously better than the comparative examples.

[0094] It can be seen from the above that, compared with the comparative example, the lithium-ion battery silicon-based negative electrode binder of each embodiment of the present invention is a three-dimensional network polymer formed by cross-linking natural polysaccharides, epichlorohydrin and lithium salts. The complex network structure can make the binder have good bonding properties, which is beneficial to maintaining the integrity of the negative electrode structure. At the same time, by introducing lithium salts, the initial coulomb efficiency of the silicon-based negative electrode can be effectively improved, the loss of positive electrode lithium ions can be reduced, and the high energy density of silicon-based materials can be exerted, thereby further improving the energy density of lithium-ion batteries. In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the comprehensive effect of the material is better.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A pre-lithiation binder, characterized in that: The raw materials of the pre-lithiation binder include natural polysaccharide, epichlorohydrin and lithium salt.

2. The pre-lithiation binder according to claim 1, characterized in that The mass ratio of the natural polysaccharide to the epichlorohydrin is 1:(2-100); and / or the mass ratio of the natural polysaccharide to the lithium salt is 1:(0.4-20).

3. The pre-lithiation binder according to claim 1 or 2, characterized in that: The natural polysaccharide includes one or more of sodium alginate, konjac glucomannan, starch, sodium hyaluronate, xanthan gum, peach gum and gum arabic; preferably, the weight average molecular weight of the natural polysaccharide is 100,000 to 2 million; and / or the lithium salt includes one or more of lithium metaborate, lithium tetraborate and lithium sulfate.

4. The method for preparing the pre-lithiation binder according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, mixing natural polysaccharides with water to obtain a first raw material solution, and adjusting the pH of the first raw material solution to 8-10; Step S2, mixing lithium salt with water to obtain a second raw material solution; Step S3, adding the second raw material solution dropwise to the first raw material solution to obtain a mixed solution; Step S4, adding epichlorohydrin to the mixed solution to carry out a cross-linking reaction to obtain the pre-lithiation binder.

5. The preparation method according to claim 4, characterized in that: In the step S1, The mass fraction of the first raw material solution is 0.1-5%; and / or the natural polysaccharide is mixed with water and then heated in a water bath at a temperature of 60-90° C.; Preferably, an alkaline aqueous solution is used to adjust the pH of the first raw material solution, and the alkaline aqueous solution includes a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution; more preferably, the molar concentration of the alkaline aqueous solution is 0.08 to 0.12 mol / L.

6. The preparation method according to claim 4 or 5, characterized in that: In step S2, the mass fraction of the second raw material solution is 1-10%; and / or In the step S3, the mass ratio of the natural polysaccharide in the first raw material solution to the lithium salt in the second raw material solution is 1:(0.4-20).

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S4, the mass ratio of the natural polysaccharide in the first raw material solution to the epichlorohydrin is 1:(2-100); and / or the temperature of the cross-linking reaction is 60-90° C., and the time is 4-10 hours.

8. A silicon-based negative electrode plate, characterized in that: The invention comprises the pre-lithiation binder according to any one of claims 1 to 3.

9. The silicon-based negative electrode plate according to claim 8, characterized in that: The weight percentage of the pre-lithiation binder in the silicon-based negative electrode plate is 5-15%.

10. A lithium ion battery, characterized in that: Comprising the silicon-based negative electrode plate as described in claim 8 or 9.